Walter Rodney : his last days and campaigns; with an introduction by Clem Seecharan - Kwayana, Eusi (R. Ferdinand-Lalljie Publishers BirminghamGB, 2012)
Presents a description of Rodney's last years in Guyana. Discusses Rodney's contribution to the struggle for bread and justice